Crude Turmeric Extract Improves the Suppressive Effects of Lactobacillus rhamnosus GG on Allergic Inflammation in a Murine Model of House Dust Mite-Induced Asthma - Ghiamati Yazdi, Fariba; Zakeri, Amin; Ark, Ingrid van; Leusink-Muis, Thea; Braber, Saskia; Soleimanian-Zad, Sabihe; Folkerts, Gert (Frontiers in Immunology, 2020)
There is a strong correlation between dysregulation of the gastrointestinal microbiota and development of allergic diseases. The most prevalent therapies for relieving asthma symptoms are associated with serious side effects, and therefore novel approaches are needed. Our objective was to elucidate whether oral administration of Lactobacillus rhamnosus GG (LGG) as a probiotic or turmeric powder (TP) as a prebiotic or both as a synbiotic mitigate allergic inflammation including lung function, airway inflammatory cell infiltration, Th2 cytokines/chemokine in a murine model of house dust mite (HDM)-induced asthma. BALB/c mice were intranasally sensitized and challenged with HDM received TP (20 mg/Kg mouse), or/and LGG (105 or 107 cfu/ml), or both orally. Interestingly, the synbiotic intervention (HDM-TP-LGG E7) specifically suppress the developement of airway hyperresponsiveness in response to methacholine. Besides, our synbiotic, TP, and LGG strongly down-regulated eosinophilia, IL-5, CCL17, IL-13. In terms of T cell response, CD4+ Th2 cells and CD4+ Th17 population were reduced in the splenocytes of the treatment groups compared to control. The synbiotic group not only elevated CD25+Foxp3+Treg frequency compared to asthmatic group, but also increased T reg cells compared to the probiotic group. The synbiotic also indicated the superior effect in suppressing Th2 cells compared to probiotic. Although, TP and LGG alone displayed suppressive effects, this study showed that the combination therapy consisting of TP and LGG (synbiotic) is more effective in some of the parameters than either of the treatments alone. This novel synbiotic, might be considered as a potential food-based drug for translational medicine and can possibly be used along with corticosteroid treatment.